Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the quadratic equation \(x^2 + 6x - 5 = 0\) and express the solutions in the form \(x = m \pm n\), follow these steps:
1. Identify the coefficients:
[tex]\[ a = 1, \quad b = 6, \quad c = -5 \][/tex]
2. Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = 6^2 - 4 \cdot 1 \cdot (-5) = 36 + 20 = 56 \][/tex]
3. Find the roots using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{56}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{56}}{2} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{56}}{2} \][/tex]
The two roots are:
[tex]\[ \text{Root 1: } x_1 = \frac{-6 + \sqrt{56}}{2} \approx 0.7416573867739413 \][/tex]
[tex]\[ \text{Root 2: } x_2 = \frac{-6 - \sqrt{56}}{2} \approx -6.741657386773941 \][/tex]
4. Determine \(m\) and \(n\) such that \(x = m \pm n\):
- \(m\) is the average of the two roots:
[tex]\[ m = \frac{x_1 + x_2}{2} = \frac{0.7416573867739413 + (-6.741657386773941)}{2} = \frac{-6}{2} = -3.0 \][/tex]
- \(n\) is the absolute value of the difference between one of the roots and \(m\):
[tex]\[ n = |x_1 - m| = |0.7416573867739413 - (-3.0)| = 3.7416573867739413 \][/tex]
So, the solutions of the equation \(x^2 + 6x - 5 = 0\) are given by:
[tex]\[ x = m \pm n \quad \text{where} \quad m = -3.0 \quad \text{and} \quad n = 3.7416573867739413 \][/tex]
[tex]\(\boxed{-3 \pm 3.7416573867739413}\)[/tex]
1. Identify the coefficients:
[tex]\[ a = 1, \quad b = 6, \quad c = -5 \][/tex]
2. Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = 6^2 - 4 \cdot 1 \cdot (-5) = 36 + 20 = 56 \][/tex]
3. Find the roots using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{56}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{56}}{2} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{56}}{2} \][/tex]
The two roots are:
[tex]\[ \text{Root 1: } x_1 = \frac{-6 + \sqrt{56}}{2} \approx 0.7416573867739413 \][/tex]
[tex]\[ \text{Root 2: } x_2 = \frac{-6 - \sqrt{56}}{2} \approx -6.741657386773941 \][/tex]
4. Determine \(m\) and \(n\) such that \(x = m \pm n\):
- \(m\) is the average of the two roots:
[tex]\[ m = \frac{x_1 + x_2}{2} = \frac{0.7416573867739413 + (-6.741657386773941)}{2} = \frac{-6}{2} = -3.0 \][/tex]
- \(n\) is the absolute value of the difference between one of the roots and \(m\):
[tex]\[ n = |x_1 - m| = |0.7416573867739413 - (-3.0)| = 3.7416573867739413 \][/tex]
So, the solutions of the equation \(x^2 + 6x - 5 = 0\) are given by:
[tex]\[ x = m \pm n \quad \text{where} \quad m = -3.0 \quad \text{and} \quad n = 3.7416573867739413 \][/tex]
[tex]\(\boxed{-3 \pm 3.7416573867739413}\)[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.